Educação infantil na rede pública de Cuiabá : análise da construção de um projeto cultural para as crianças de até 3 anos, ambiguidades do percurso - Lorensini, Sandra Regina Geiss (2018)
This research aimed to analyze the Social Representations of a group of teachers, accompanying children up to 3 years old, on the pedagogical work in the context of Early Childhood Education - daycare centers, in an attempt to identify the content of these representations based on the interface of two forces that compose them, the contents that circulate in our society elaborated in the daily practice and the forces derived from the scientific knowledge disseminated during teacher training processes. In Cuiabá in 2009, the Pedagogical Proposal for Early Childhood Education was launched, which in addition to confirming the inseparability of care and education in daycare centers, launches guiding principles around the pedagogical organization for the education of children in daycare centers and nursery schools, based on playfulness, spatial arrangements and narratives. In the universe of the theory of social representations (MOSCOVICI, 2003; JODELET, 2005; JOVCHELOVITCH, 2007; 2008), the adoption of scientific principles and their integration into common sense notions by different communities or groups reflects a possibility of transformation of abstract and conceptual ideas in more accessible images, metaphors, concrete objects and habitual practices. (BAUER; GASKELL, 2002). Thus, the Proposal of Early Childhood Education in the city of Cuiabá was considered as a policy with principles and categories that support a pedagogical work proposal for Early Childhood Education as a propitious scenario for the emergence and circulation of Social Representations. In the search for having access to representational contents of teachers involved in the daycare universe, this research assumes a qualitative and quantitative-qualitative basis, involving research and analysis in three dimensions: the transubjective dimension consisted of documentary analysis, evidencing theoretical and methodological aspects around the reference points of Early Childhood Education – daycare centers for Cuiabá; the intersubjective dimension, which through participant observation in two daycare centers involved the nursery education professionals who directly fulfill differentiated roles in relation to the dynamization of the child's education up to three years and the third dimension, the subjective dimension, sought through interviews, to access the social representations of the teachers about the pedagogical work, in its theoretical and methodological aspects, whose guidelines are found in the Pedagogical Proposal of Early Childhood Education of the municipality. Based on the analyzes carried out, it is possible to indicate that there are fragile representational contents around pedagogical guidelines for daycare centers, and that knowledge and actions are strongly hidden by the dynamics of routines, conceptually the pedagogical work is fragile, justified greatly by the difficulties and day-to-day limitations in daycare centers and in relations with the municipal education system. The work with children's narratives, even if conforming in small scales of quotation of stories chosen and directed almost exclusively by teachers, approaches as a methodological alternative for the accomplishment of didacticpedagogical actions. This proposition, however, is not confirmed in the spaces of the daycare centers and based on what is not told but is lived in the day care centers, this study confirms that there is a greater concentration of moments around activities of care with hygiene, food and physical comfort, which are established routines. It can be inferred that the exclusive position of caregiver in a significant number of teachers is strongly associated with the fragile representational contents around the pedagogic practice, as well as with the limits placed by the public education system with regards to the job and career plan, when it considers them and legally denominates them as Child Development Technician – TDIs, to the detriment of Teachers of Early Childhood Education.